Introduction. - Rabin, Dana Y.; Surowitz-Israel, Hilit (Shofar: An Interdisciplinary Journal of Jewish Studies, 2025)
Over the past two decades, there has been an increased focus on the Jews of the Caribbean. As this special cluster demonstrates, an intersectional approach which considers migration, diaspora, race, and ideas of home helps frame the Jews of the Caribbean within broader sociohistorical trends. The Jews of the Caribbean Basin provide scholars with a generative site to consider the intersection of race and religion.